2020
DOI: 10.1038/s41467-020-16944-9
|View full text |Cite
|
Sign up to set email alerts
|

Author Correction: Comprehensive aptamer-based screening identifies a spectrum of urinary biomarkers of lupus nephritis across ethnicities

Abstract: An amendment to this paper has been published and can be accessed via a link at the top of the paper.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…ALCAM expression was also up-regulated in the glomeruli and tubules of MRL/lpr lupus-like murine model (33). In recent high-throughput proteomic approaches, urine ALCAM showed promise in predicting LN activity in SLE patients (30). Further validation in two aSLE cohorts confirmed the higher urine ALCAM levels with significant correlations with total and renal SLEDAI scores (34,35).…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…ALCAM expression was also up-regulated in the glomeruli and tubules of MRL/lpr lupus-like murine model (33). In recent high-throughput proteomic approaches, urine ALCAM showed promise in predicting LN activity in SLE patients (30). Further validation in two aSLE cohorts confirmed the higher urine ALCAM levels with significant correlations with total and renal SLEDAI scores (34,35).…”
Section: Discussionmentioning
confidence: 87%
“…Based on the correlation analysis (Figure 1B) and the unsupervised Bayesian network analysis (Figure 5), urine ALCAM is likely driving the biomarker potential of VCAM1 and PF4. Indeed, Bayesian analysis also identified urine ALCAM as a driving factor in dictating the expression profiles of other urine markers in aSLE (30). ALCAM, also known as cluster of differentiation-166 (CD-166) is a cell adhesion glycoprotein that is highly expressed on antigen-presenting cells and shows a fundamental role in mediating immune cell adhesion and migration, co-stimulation of T-cells and sustaining T cell activation.…”
Section: Discussionmentioning
confidence: 99%
“…With the rapid development of single-cell RNA sequencing (scRNA seq) and its application in the profiling of genes associated with SLE or LN (164)(165)(166), more novel biomarkers or biomarker panels may be emerging. However, these gene expression data must be validated at the protein level before moving to biomarker detection in clinical settings.…”
Section: Biomarker Panels For Sle: the Destinationmentioning
confidence: 99%
“…Moreover, these tests have been studied most in patients with lupus nephritis and their utility in detecting other manifestations of SLE is less clear. More comprehensive tools that integrate novel biomarkers, identified by longitudinal analyses of well-characterized cohorts and the use of new big data analytical techniques, such as machine learning, could be valuable for capturing disease activity and providing timely stratification of patients based on the unified pattern of dysregulated pathways (41,42). Transcriptomic studies have identified distinctive signatures in SLE blood samples that include type I interferons (IFN), as well as myeloid and B cell-related (plasma cell) signatures (43)(44)(45)(46).…”
Section: Challenges In Established Disease Disease Activitymentioning
confidence: 99%
“…Transcriptomic studies have identified distinctive signatures in SLE blood samples that include type I interferons (IFN), as well as myeloid and B cell-related (plasma cell) signatures (43)(44)(45)(46). Several studies also showed a correlation between these signatures and disease activity (42)(43)(44). Although a robust interferon gene signature (IGS) has been demonstrated in both blood and affected tissues of SLE patients (47), no apparent correlations have been found between the IGS and disease activity in longitudinal studies (46,48,49).…”
Section: Challenges In Established Disease Disease Activitymentioning
confidence: 99%